Inclination of keris research theme according to colonial scholars perspective - Mohd. Zafri, Muzaffar; Hamdan, Rahimah; Sujud, Arba'ie; Ahmad, Abdul Muati@Zamri (Human Resources Management Academic Research Society, 2023)
This study explores the inclination of keris research theme as a significant weapon in the traditional Malay community until now. The discussion focuses on the main function of keris as a weapon and how it evolved to become a symbol of identity for the Malay community that attracted the interest of colonial scholars, especially the British in the 19th century AD, in researching and understanding the relationship between the weapon and the colonised society. This study will complete two objectives which is to analyse the themes of research regarding keris in the colonial era and to deduce the tendency of these themes based on the opinions of several renowned colonial scholars. The research methodology is a bibliographic analysis of several scientific journals by colonial scholars in the 19th century AD on Malay keris, especially on the Journal of the Malayan Branch of the Royal Asiatic Society and some others. The results revealed that the themes associated with the study of keris by colonial scholars mainly focus on non-physical properties, such as mystical elements and beliefs on keris. These past studies were also found to have an influence over the mentality and way of thinking of the Malay community today. In conclusion, research works on keris as a weapon that is synonymous with the Malay identity need to be intensified so that more rational and relevant findings can be highlighted in order to reduce the dependency on studies by Western scholars, which are often biased and have their own interests.